2020
DOI: 10.1542/hpeds.2020-0094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Social Risks on Inpatient Screening and Their Impact on Pediatric Care Use

Abstract: OBJECTIVES: Screening for social determinants of health in the inpatient setting is uncommon. However, social risk factors documented in billing and electronic medical record data are associated with increased pediatric care use. We sought to describe (1) the epidemiology of social risks and referral acceptance and (2) association between social risks identified through routine inpatient screening and care use. METHODS: Paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…However, quantitative studies of screening effectiveness in the inpatient setting remain limited. The largest studies showed that about one-third of families were identified as having positive SDOH screens, and this was found to be increased in children with medical complexity [55,56]. Frequent and extended hospitalizations in children with medical complexity resulting in high per capita healthcare costs makes the inpatient setting an important opportunity to recognize and address SDOH.…”
Section: Acute Care Settingsmentioning
confidence: 99%
“…However, quantitative studies of screening effectiveness in the inpatient setting remain limited. The largest studies showed that about one-third of families were identified as having positive SDOH screens, and this was found to be increased in children with medical complexity [55,56]. Frequent and extended hospitalizations in children with medical complexity resulting in high per capita healthcare costs makes the inpatient setting an important opportunity to recognize and address SDOH.…”
Section: Acute Care Settingsmentioning
confidence: 99%
“…For instance, despite higher socioeconomic status than parents of children with noncomplex chronic disease, parents of CMC more commonly report financial and social hardships 4 . Parents are also more likely to report health‐related social needs on routine inpatient screening 5 . CMC utilizes significantly more social work services in a medical setting than nonmedically complex children 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Parents are also more likely to report health-related social needs on routine inpatient screening. 5 CMC utilizes significantly more social work services in a medical setting than nonmedically complex children. 6,7 Previous work has suggested that certain patient-or family-level factors like public insurance, non-White race, and barriers to consistent follow-up influence risk of preventable hospitalizations and more hospital bed-days.…”
Section: Introductionmentioning
confidence: 99%
“…This separation of models may explain why many of the SES factors we considered were not associated with readmission in final models, despite many prior studies demonstrating their importance as risk factors for pediatric readmission. 25 , 26 Many SES factors we considered are likely stable during a 6-month period and may not be relevant for those with preceding care, as for the RAM cohort. In fact, only Black race and Hispanic ethnicity were associated with lower readmission risk in the cohort without prior utilization (NAM).…”
Section: Discussionmentioning
confidence: 99%